Building institutional capacity: more accountability than autonomy? - Mertkan, Sefika; Sugrue, Ciaran (Emerald Group Publishing Ltd, 2014)
Purpose - The purpose of the paper is to explore the strategies schools use to build capacity in English secondary schools where they operate under strong pressures to improve continuously and failure to do so carries severe penalties. Design/methodology/approach - The approach involved in-depth case studies of six schools that utilized multiple sources of evidence. These include policy documents, interviews with multiple actors and observations of key management meetings. Findings - Findings suggest travelling strategies used by schools, but these are implemented with varying intensity, hybridity and creativity. The common travelling strategies re-contextualized in organizational fields are data workmanship, multi-level monitoring, and performance development. For participating schools, successfully replicating these three pillars through identity cloning, an attempt to establish institutional identities identical to that of the performing schools, helps lift schools in different contexts. Originality/value - There has been ample discussion on organizational capacity building, but the evidence on the actual strategies schools use is thin. This paper contributes to knowledge generation and understanding by providing as complete a picture as possible of the strategies schools use while remaining skeptical regarding the long-term consequences of short term gains.
Keywords: Accountability; Capacity building; Autonomy; Organizational improvement